Bringing objectivity and predictability to one of the most diverse and opiniated sports in the world by leveraging data - Sousa, David Silva de (2022)
Internship Report presented as the partial requirement for obtaining a Master's degree in Data Science and Advanced Analytics, specialization in Data Science